Surveillance in the Digital Age - Nishnianidze, Anri (European Scientific Journal, ESJ, 2024)
Purpose: As technology advances, electronic devices have become ubiquitous among individuals of all backgrounds. From mobile phones to computing devices, people rely on these tools on a daily basis for both personal and professional purposes. The presented research seeks to investigate the extent to which individuals are being monitored in the digital realm and identify solutions to safeguard citizens from the threat of mass surveillance. Findings: In the modern era, it is common for people to utilize various devices for a multitude of purposes, such as search engines and social networks. However, many are unaware that the information they share online is not always erased from cyberspace. This study aims to shed light on how this data is obtained and utilized and the potential risks humanity faces if privacy is not safeguarded in the digital age. Research limitations/implications: The objective of this research is to thoroughly examine the current scientific literature, studies, and articles regarding the perils of surveillance in the digital era. The paper aims to highlight the challenges associated with combating surveillance. In the concluding section of the analysis, a concise set of recommendations will be provided, which are crucial to uphold in order to safeguard individuals’ constitutional rights in the face of the potential ramifications of streamlined surveillance. Originality/value: In today’s digital age, it has become almost universal for people to communicate through electronic devices in cyberspace, whether for work or personal purposes. Unfortunately, this environment is often not secure, and automated surveillance models can be used to acquire people’s data without their knowledge or consent. This raises serious concerns about privacy and the protection of fundamental human rights. That is why it is essential to conduct research that sheds light on the means of surveillance and explores ways to fight against it.